(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
It was shown the possibility of modification of carbon electrode with silica and haemoglobin based thin film using method of electrodeposition. The optimal conditions of electrode modification under which stable homogeneous coating was obtained were determined, i.e. concentration of cationic surfactants and haemoglobin in the silica sol, potential and time of electrodeposition. Haemoglobin encapsulated in the film obtained under these conditions was electrochemically and catalytically active.